Public Policy and Economic Transformation: Bridging Growth, Equity, and Environmental Sustainability - Akbar Jalil Al Kareem (PT. Islamic Research Publisher, 2025)
Public policy has become a decisive instrument for addressing the increasingly complex relationship between economic growth, social equity, and environmental sustainability. While governments have pursued various development strategies to stimulate economic performance, persistent income disparities and ecological degradation continue to undermine the effectiveness of existing policy frameworks. This study aims to examine how public policy can simultaneously promote economic transformation, equitable development, and environmental sustainability through an integrated governance approach. Employing a qualitative field research design, the study collected empirical data through semi-structured interviews with policymakers, local government officials, business actors, and community representatives, complemented by direct observation and analysis of policy documents. The data were analyzed using thematic analysis supported by triangulation to ensure the credibility and consistency of the findings. The results demonstrate that economic transformation is more effective when public policies integrate economic, social, and environmental objectives rather than prioritizing growth alone. The study identifies three critical determinants of successful policy implementation: participatory governance involving multiple stakeholders, evidence-based policy formulation supported by reliable socioeconomic and environmental data, and adaptive institutional capacity to respond to changing development challenges. Furthermore, the findings reveal that policies emphasizing inclusive economic participation, green investment, and sustainable resource management generate broader socioeconomic benefits while reducing environmental risks. Nevertheless, institutional fragmentation, uneven administrative capacity, and limited cross-sectoral coordination remain significant obstacles to achieving balanced development outcomes. This research contributes to the literature by proposing an integrated public policy framework that bridges economic growth, distributive equity, and environmental sustainability within a single governance paradigm. The study extends contemporary public policy scholarship by demonstrating that sustainable economic transformation depends not only on market efficiency but also on institutional coherence, collaborative governance, and long-term policy integration, thereby offering practical implications for policymakers pursuing inclusive and resilient development.